Clinical application of light solidified calcium hydroxide as temporary crown adhesive - PANG Jikai; NIE Ermin; HUANG Daiying (口腔疾病防治, 2017)
Objective To investigate the feasibility of using UV curable calcium hydroxide as temporary crown binder. Methods 242 patients with temporary crown were selected and randomly divided into three groups according the order of registration week each month, and respectively underwent temporary crown cement with TempoCemNE (n = 78), Provicol (n = 80) and Calcimol LC (n = 84) for each tooth. The retention effect and the status of the gum and the pulp were observed at one week after operation. Results There was no significant difference between the three groups in the retention effect and the status of the gum and the pulp (c1 2 = 5.553, P1 = 0.062 > 0.05; c2 2 = 4.783, P2 = 0.091 > 0.05; c3 2 = 3.290, P3 = 0.193 > 0.05). Conclusion There was a good effect of temporary crown cement in three groups of TempoCemNE, Provicol and Calcimol LC. Calcimol LC can be used as a new type of temporary crown cement with good bonding performance and the protection to gums and pulp, and simple operation.